Wajah Pendidikan Matematika SD di Papua Ditinjau dari Minat, Motivasi Belajar, dan Dukungan Keluarga - Andris Kristiono; Harsono, Harsono (Jurnal Didaktika Pendidikan Dasar, 2024)
This research aims to photograph the condition of mathematics education in elementary schools in the Papua region. The research focus involves three main aspects: student interest in learning, learning motivation, and parental support. This research focuses on mathematics education in elementary schools. The main question is how students’ learning interests, learning motivation, and parental support influence the quality of mathematics learning. This research aims to understand the role of students’ learning interests, learning motivation, and parental support in improving the quality of mathematics education in Papuan elementary schools. This research uses a qualitative approach with interviews, observation, and document analysis as data collection methods. Respondents included students, parents, and teachers at Papua Elementary Schools. Data were analyzed using a descriptive and thematic approach. The research results describe students’ interest in learning, motivational factors, and the role of parental support in learning mathematics. It is hoped that the results of this research can provide insight into the development of basic education in Papua and improve the quality of mathematics learning in elementary schools.